Prediction of cutting force by using finite element method in end-milling of AISI 1018 medium carbon steel - Tomadi, Siti Haryani; Mokhtar, Suhaily; Hassan, Mas Ayu; Daud, Rosdi (The Mattingley Publishing Co., Inc., 2020)
The objective of this paper are to predict the cutting force using predictive model of finite element method (FEM) and validate thru experiments, and to analyze the influence of cutting parameters during the circular end milling of AISI 1018 medium carbon still employing uncoated carbide tool. Three level of cutting speed, feed rate and depth of cut are designed accordingly. Result of cutting forces is evaluated and validated. Analysis also been made by considering the percentage of error in FEM and experimental work by Dynoware Software. The results obtained by simulation using Abaqus software and experimental work, it shows small percentage of error and it is suggested that the predictive model is reliable whereas the FEM value captures the qualitative trends fairly well in regard to the change of cutting speed, feed rate and depth of cut